Investigating the Mechanical Properties of Natural Fiber-Reinforced Concrete with Kenaf, Jute, and Coconut Fibers (Journal of Civil Engineering Researchers, 2024)
This study investigates the mechanical properties of natural fiber-reinforced concrete (FRC) through the addition of natural fibers such as kenaf (KFRC), jute (JFRC), and coconut (CFRC). The evaluation focused on key properties including compressive strength, split tensile strength, and flexural strength. Fiber combinations were introduced in a fiber volume fraction of 0.5%, with fiber lengths standardized at 20 mm. A water-to-binder ratio of 0.44 was maintained for all mixes. Six specimens were tested for each parameter after a curing period of 28 days. The objective of this research was to assess the potential of natural fibers like kenaf, jute, and coconut for developing sustainable FRC while maintaining or improving its mechanical properties. Results demonstrated that the inclusion of natural fibers at the specified length and concentration positively influenced post-cracking flexural performance and splitting tensile strength. Among the tested combinations, FRC reinforced with jute fibers (JFRC) exhibited superior performance compared to other fiber combinations.
Keywords: Natural fiber-reinforced concrete; Kenaf fibers; Jute fibers; Coconut fibers; Sustainable concrete